The emerging technology of tissue engineering : Focus on stem cell niche - Schlötzer-Schrehardt, Ursula; Freudenberg, U.; Kruse, Friedrich (Ophthalmologe, 2017)
Limbal stem cells reside in a highly specialized complex microenvironment that is known as the stem cell niche, an anatomically protected region at the bottom of the Palisades of Vogt, where the stem cells are located and where their quiescence, proliferation and differentiation are maintained in balance. Besides the epithelial stem and progenitor cell clusters, the limbal niche comprises several types of supporting niche cells and a specific extracellular matrix mediating biochemical and biophysical signals. Stem cell-based tissue engineering aims to mimic the native stem cell niche and to present appropriate microenvironmental cues in a controlled and reproducible fashion in order to maintain stem cell function within the graft. Current therapeutic approaches for ex vivo expansion of limbal stem cells only take advantage of surrogate niches. However, new insights into the molecular composition of the limbal niche and innovative biosynthetic scaffolds have stimulated novel strategies for niche-driven stem cell cultivation. Promising experimental approaches include collagen-based organotypic coculture systems of limbal epithelial stem cells with their niche cells and biomimetic hydrogel platforms prefunctionalized with appropriate biomolecular and biophysical signals. Future translation of these novel regenerative strategies into clinical application is expected to improve long-term outcomes of limbal stem cell transplantation for ocular surface reconstruction.
EVALuna2:21332